Multiphase and pore scale modeling on catalyst layer of high-temperature polymer electrolyte membrane fuel cell - Duan, Kangjun; Zhu, Lijun; Li, Min; Xiao, Liusheng; Bevilacqua, Nico; Eifert, László; Manke, Ingo; Markötter, Henning; Zhang, Ruiming; Zeis, Roswitha; Sui, Pang Chieh (Journal of The Electrochemical Society, 2021)
Phosphoric acid as the electrolyte in high-temperature polymer electrolyte membrane fuel cell plays an essential role in its performance and lifetime. Maldistribution of phosphoric acid in the catalyst layer (CL) may result in performance degradation. In the present study, pore-scale simulations were carried out to investigate phosphoric acid’s multiphase flow in a cathode CL. A reconstructed CL model was built using focused ion beam-SEM images, where distributions of pore, carbon support, binder, and catalyst particles can be identified. The multi-relaxation time lattice Boltzmann method was employed to simulate phosphoric acid invading and leaching from the membrane into the CL during the membrane electrode assembly fabrication process. The predicted redistribution of phosphoric acid indicates that phosphoric acid of low viscosity or low wettability is prone to leaching into the CL. The effective transport properties and the active electrochemical active surface area (ECSA) were computed using a pore-scale model. They were subsequently used in a macroscopic model to evaluate the cell performance. A parametric study shows that cell performance first increases with increasing phosphoric acid content due to the increase of ECSA. However, further increasing phosphoric acid content results in performance degradation due to mass transfer limitation caused by acid flooding.
CRIS-Team Scopus Importer:2023-08-01